A court of silver flames [large type] - Maas, Sarah J. (Maas, Sarah J. Court of thorns and roses, 2025)
"Ever since becoming High Fae against her will, Nesta Archeron has struggled to find a place for herself within the strange, deadly world she inhabits. The one person who ignites her temper more than any other is Cassian, but the fire between them ins undeniable and only burns hotter as they are forced into close quarters with each other. Meanwhile, human queens have forged a dangerous new alliance, threatening the fragile peace that has settled over the realms. Nesta and Cassian battle monsters from within and without as they search for acceptance -- and healing -- in each other's arms."